The imperative for cross-cultural medical education in globalized healthcare - Mohiyeddini, Changiz (Frontiers in Psychology, 2024)
Current healthcare systems are like living creatures. They are highly complex, multifaceted, and dynamic. They must constantly change and adapt; they are like a melting pot, brimming with both rich and diverse cultures from all corners of the world. Beyond just nationality, these systems can include many languages, religious beliefs, socioeconomic backgrounds, and unique health practices. The tides of globalization, multicultural societies, migration, and international collaboration are continuously reshaping how healthcare providers are educated and how healthcare is delivered in an equitable, inclusive, and fair manner. To keep pace with, and within, these highly vibrant sociocultural frameworks, Cross-Cultural Medical Education is needed to educate healthcare professionals. This education is essential to create professionals who are not just skilled, but who are also culturally savvy and able provide fair and equal care to patients from all sorts of backgrounds. It provides professionals with foundational knowledge to navigate the complex landscape of diverse patient populations. Cross-Cultural Medical Education is thus of paramount importance to satisfy the need for effective cross-cultural communication and understanding in patient care preferences, ultimately leading to improved health outcomes.